Novel azole-urea hybrids as VEGFR-2 inhibitors: Synthesis, in vitro antiproliferative evaluation and in silico studies - KULABAŞ, NECLA; DANIŞ, ÖZKAN; KÜÇÜKGÜZEL, İLKAY (My University, 2023)
The vascular endothelial growth factor receptor-2 (VEGFR-2) is a receptor tyrosine kinase known to be abnormally expressed in various malignant tumors, including breast cancer, and is considered one of the most important contributors to tumor angiogenesis. Sorafenib is one of many VEGFR-2 inhibitors that have received approval for clinical use from the US FDA in recent years. Accordingly, in this study, the synthesis of two new pyrazoles, six 1,3,4-oxadiazoles, four 1,3,4-thiadiazoles, and ten 1,2,4-triazole-3-thione derivatives having structural characteristics similar to sorafenib was carried out. A preliminary screening of synthesized compounds and known inhibitors sorafenib and staurosporine at 10 µM concentration on in vitro activity of VEGFR-2 was performed, and compounds 10c, 8a, and 11 g were identified as the most potent derivatives with% VEGFR-2 residual activities lower than 30%, and dose-dependent inhibition studies was carried out to determine the IC50 values of these inhibitors. Compound 10c was found to be the most potent inhibitor of VEGFR-2 activity with an IC50 value of 0.664 µM. The anti-proliferative activity of synthesized derivatives was assessed against a breast carcinoma (MCF-7) cell line, a triple negative human breast adenocarcinoma (MDA-MB-231) cell line, and noncancerous fibroblast cells (L929). Compound 8a displayed superior activity when compared to sorafenib against MCF-7 (7.69 fold) and MDA-MB-231 (1.52 fold) cell lines while displaying 3.75-fold less toxicity against the normal L929 cell line. Annexin V binding assay revealed that compound 8a significantly increased early and late apoptosis in MCF-7 cells and late apoptosis and necrosis in MDA-MB-231 cells. Computational studies such as molecular docking and ADMET evaluation were performed to elucidate the binding interactions and drug-likeness of the synthesized compounds. The results indicate that compound 8a could be a promising candidate for the development of a novel anti-angiogenic and anti-proliferative agent.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; 1,2,4-triazole-3-thione; 1,3,4-oxadiazoles; 1,3,4-thiadiazoles; Anti-cancer; Pyrazole; VEGFR-2 inhibitor